La alteración del orden del día para aprobar las leyes de referéndum y transitoriedad. El uso del artículo 81.3 del Reglamento del Parlamento de Cataluña - Fernández Cañueto, Daniel (Revista de Derecho Político, 2018)
Resumen: La presente investigación trata de analizar el uso que se hizo del artículo 81.3 del Reglamento del Parlamento de Cataluña para alterar el orden del día y aprobar tanto la proposición de ley de referéndum como la de transitoriedad. Para ello, primero se ha examinado tanto el contenido que posee dicho artículo como aquellas cuestiones dudosas sobre el mismo. En segundo lugar, se ha resumido tanto la interpretación que se le dio a dicho precepto por la mayoría parlamentaria catalana para poder introducir ambas proposiciones de ley como las consecuencias que ello tuvo en forma de recursos de amparo. En tercer lugar, se ha contrastado la jurisprudencia del Tribunal Constitucional con las diferentes cuestiones planteadas durante el procedimiento de aprobación de ambas proposiciones de ley. En cuarto lugar, se ha intentado realizar una propuesta de resolución de aquellos recursos de amparo presentados por el grupo parlamentario de Ciudadanos sobre los que el Tribunal Constitucional todavía no se ha pronunciado. Y, en quinto y último lugar, se han analizado las SSTC 10/2018 y 27/2018 que resuelven los recursos de amparo sobre los acuerdos de la Mesa por los que se desestimaba la solicitud de dictamen del CGE. Una vez realizado todo ello, seis han sido las principales conclusiones. Uno: que la Mesa del Parlamento de Cataluña tenía tanto la obligación de realizar un análisis más allá de la estricta verificación de los requisitos formales por existir unos incidentes de ejecución que le obligaban expresamente a ello, como el deber de acordar su inadmisión por ser las proposiciones de ley palmaria y evidentemente inconstitucionales. Dos: que el Tribunal Constitucional debería fallar en contra de la parte del recurso de Ciudadanos donde se pedía anular los acuerdos del Pleno mediante los cuales se alteró el orden del día, pero debería resolver a favor de aquella otra parte del mismo recurso donde se pedía anular los acuerdos del Pleno mediante los cuales se creó un procedimiento legislativo ad hoc a través del art. 81.3 RPC. Tres: que las SSTC 10/2018 y 27/2018 estiman positivamente los recursos de amparo del grupo parlamentario Socialista en los que se pedía declarar la nulidad tanto de los Acuerdos de la Mesa de los días 6 y 7 de septiembre por los que se desestimaba tramitar la solicitud de dicho dictamen como de sus efectos. Cuatro: que no parece ser manifiestamente inconstitucional que a través del art. 81.3 RPC se pueda modificar el orden del día para incluir el debate y votación de una proposición de ley, afirmación esta que bien puede ser ampliable a todos aquellos preceptos de los demás reglamentos parlamentarios cuyo contenido sea similar. Cinco: que ni el art. 81.3 RPC ni ningún otro precepto que desarrolle la alteración del orden del día en los demás reglamentos parlamentarios, habilita para que a su través la mayoría parlamentaria cree un procedimiento legislativo ad hoc gracias al cual posteriormente se puedan aprobar proposiciones de ley. Y seis: que el motivo principal por el cual se acabaron tramitando las proposiciones de ley de esa manera no es otro que la voluntad de la mayoría parlamentaria (y, por ende, del Gobierno catalán) de tramitar y aprobar con apariencia de legalidad dos proposiciones de ley que eran ya en su origen evidentemente inconstitucionales. Summary: 1. Introduction. 2. The content of article 81.3 Of the standing orders of the parliament of catalonia. 3. The consequences of the use of article 81.3 Rpc to introduce the laws of referendum and transitoriness on the agenda. 4. The jurisprudence of the constitutional court on the questions raised during the procedure to approve both bills. 4.1 The problem of whether the Parliamentary Bureau could have inadmitted to process both bills. 4.2 The problem of whether art. 81.3 RPC allows through it to develop that legislative procedure that was eventually used to approve both bills. 4.3 The problem regarding the suppression of the possibility of requesting a Dictum from the Council of Statutory Guarantees. 5. A possible resolution of the appeal submitted by the ciudadanos parliamentary group. 5.1 In relation to the plenary agreements by means of which the agenda was changed to introduce the bills of the referendum and of transitoriness. 5.2 In relation to the agreements of the Plenary through which an ad hoc legislative procedure was created to proceed to the debate and definitive voting of the bills of the referendum and of transitoriness. 6. The SSTC 10/2018 and 27/2018 that solve the appeal in relation to the agreements of the parliamentary bureau that rejected the request for the CGE’s dictum. 7. Conclusion. Abstract: The present investigation tries to analyse the use that was made of article 81.3 of the Catalan Parliamentary rules of procedure to alter the order of the day and approve both the Referendum Law and the Transitoriness Act. For this, first the content of the article as well as the dubious questions about it have been examined. Secondly, the interpretation given to this precept by the Catalan parliamentary majority in order to introduce both bills as well as the consequences that it had in the form of appeals has been summarized. Thirdly, the jurisprudence of the Constitutional Court has been contrasted with the different issues raised during the approval procedure of the Referendum and Transitoriness Acts. Fourthly, an attempt has been made to make a proposal for a resolution of the appeals filed and on which the Constitutional Court has not yet ruled. And fifthly, analyse the STCC 10/2018 and 27/2018 that solve the appeal in relation to the agreements of the Parliamentary Bureau that rejected the request for the CGE’s dictum. Once all this has been done, six have been the main conclusions. One: that the Catalan Parliament Bureau was so obliged to carry out an analysis beyond the strict verification of the formal requirements because there were some execution incidents that expressly obliged it, as well as the duty to agree on its inadmissibility because the proposals were of obvious law and evidently unconstitutional. Two: that the Constitutional Court should rule against the part of the Citizens’ appeal where it was requested to annul the agreements of the Plenary by means of which the agenda was altered, but it should resolve in favour of that other part of the same resource where it was requested cancel the agreements of the Plenary through which an ad hoc legislative procedure was created through art. 81.3 RPC. Three: that the SSTC 10/2018 and 27/2018 positively estimate both the appeal of the Socialist parliamentary group and one of the parties to the appeal for protection of Citizens, in which it was requested to declare the nullity of both the Agreements of the Bureau of the 6th and September 7 for which it was rejected to process the request for such opinion and its effects. Four: it does not seem to be manifestly unconstitutional that, through art. 81.3 RPC, the agenda can be modified to include the debate and vote on a proposed law, an affirmation that may well be extended to all those precepts of the other regulations parliamentarians whose content is similar. Five: that neither art. 81.3 RPC nor any other precept that develops the alteration of the agenda in the other parliamentary regulations, enables the parliamentary majority to create an ad hoc legislative procedure through which subsequent proposals can be approved. Of law. And six: that the main reason why they ended up processing the proposals of law in this way is none other than the will of the Catalan parliamentary majority (and, thus his government) to process and approve with appearance of legality two propositions of law that were already in their origin evidently unconstitutional.